7.3: Invited Paper: Integration of large‐area optical imagers for biometric recognition and touch in displays. (24th February 2021) - Akkerman, Hylke; Peeters, Bart; van Breemen, Albert; Shanmugam, Santhosh; Lopez, Leslye Ugalde; Tordera, Daniel; van de Ketterij, Richard; Delvitto, Ezequiel; Malinowski, PaweƗ; Ke, Tung-Huei; De Roose, Florian; Hagelsieb, Luis Moreno; et al.
Abstract : In recent years there is an increasing interest to integrate optical sensing in mobile displays, for instance, for biometric fingerprint scanning functionality. There are several routes to incorporate optical fingerprint functionality within the full display area, each with their own benefits and challenges. Here we investigate the different integration routes using large‐area, ultrathin imagers based on organic photodiodes.